Electrodeposition of iron phosphide film for hydrogen evolution reaction. (10th December 2020) - Lu, Zhi-peng; Sepunaru, Lior
Abstract: The hydrogen evolution reaction (HER) by electrochemical water splitting is part of a sustainable and scalable process to produce H2 . Hence, the design of a highly efficient and low-cost electrocatalyst is in demand. We report the development of a straightforward and cost-effective method to electrodeposit an iron phosphide (FeP) film on a copper electrode at room temperature. The as-deposited FeP film was able to support current density of −10 mA/cm 2 at overpotentials of 66 mV in 0.5 M sulfuric acid (H2 SO4, pH=0.3), 131 mV in 1.0 M phosphate buffer (PB, pH=6.4) and 110 mV in 1.0 M potassium hydroxide (KOH, pH=14.0) solution, as well as a Tafel slope of 55 mV/dec, 108 mV/dec, 60 mV/dec, respectively. The film has excellent stability during HER catalysis under acidic and neutral conditions, as shown by electron microscopy and X-ray photoelectron spectroscopy.